Odpowiedź :
Odpowiedź:
[tex]\huge\boxed{\boxed{y=2(x+1\frac{3}{4})^2-3\frac{1}{8}}}[/tex]
Szczegółowe wyjaśnienie:
Postać kanoniczna funkcji kwadratowej
[tex]y=a(x-p)^2+q\\\\p=\frac{-b}{2a}\\\\q=\frac{-\Delta}{4a} \ (\Delta=b^2-4ac)[/tex]
Obliczenia
[tex]y=2x^2+7x+3\\\\a=2, \ b=7, \ c=3\\\\\Delta=7^2-4\cdot2\cdot3=49-24=25\\\\p=\frac{-7}{2\cdot2}=\frac{-7}{4}=-1\frac{3}{4}\\\\q=\frac{-25}{4\cdot2}=\frac{-25}{8}=-3\frac{1}{8}\\\\y=2(x-(-1\frac{3}{4}))^2+(-3\frac{1}{8})\\\\y=2(x+1\frac{3}{4})^2-3\frac{1}{8}}[/tex]